Meteorological Drought Preparedness Analysis for the Early 2026 Dry Season in South Kalimantan Based on BMKG Rainfall Prediction and SPI Data - Dita Mahalleni; Rosalina Kumalawati (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
Operational climate information is essential for rapidly interpreting meteorological drought risk at the beginning of the dry season. This study aims to analyze recent meteorological and climatological conditions in South Kalimantan using rainfall prediction, rainfall characteristic prediction, and the three-month Standardized Precipitation Index (SPI) for June-August 2026. A quantitative descriptive method was applied using secondary data from BMKG, the South Kalimantan Climatological Station, and relevant regional climate-change literature. The results show that July 2026 rainfall in South Kalimantan is dominated by the low category, covering 95.9% of the province, while 4.1% is predicted to be in the medium category. Rainfall characteristics are predicted to be 100% below normal, and the three-month SPI indicates that 85.5% of the region is classified as slightly dry to extremely dry. The Indonesian mean air-temperature anomaly in June 2026 reached +0.7°C, emphasizing the importance of monitoring evaporation and water demand. These findings highlight the need for early preparedness in agriculture, clean water supply, land-fire prevention, and climate-based water-resource management.